Pemanfaatan Kulit Ubi Jalar Ungu (Ipomoea batatas L.) dalam Pembuatan Nata De Batatas - Fahira Gafar; Yoakhim Y.E. Oessoe; Jolanda Ch.E. Lamaega (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
Nata de batatas is a product of purple sweet potato peel. The presence of anthocyanin compounds in purple sweet potato skin makes this food very attractive to be processed into nata products that have functional value. The purpose of this research was to determine the yield of nata from purple sweet potato peel made with variations in the percentage of purple sweet potato peel extract and the percentage of coconut water and pellicle thickness, evaluate organoleptic properties including texture, color, aroma, taste, and determine anthocyanin levels. The results showed that the highest nata yield was 70.08%. The thickness of the largest 1.26 cm. The best anthocyanin analysis in nata was 0.47 mg. The organoleptic test showed that the color percentage of purple sweet potato peel extract and the percentage of coconut water were significantly different while the texture, aroma and taste were not significantly different. Keywords: nata de batatas, purple sweet potato skin, coconut water, anthocyanin